Finding a place for corifollitropin within the PIVET FSH dosing algorithms - Yovich, John; Keane, Kevin; Borude, G.; Dhaliwal, S.; Hinchliffe, P. (Elsevier Ltd, 2017)
PIVET recombinant FSH (rFSH) dosing algorithms have been designed for rFSH injection pens, providing optimal pregnancy and live birth productivity rates whilst minimizing risk and occurrence of ovarian hyperstimulation syndrome (OHSS). Recently, long-acting recombinant gonadotrophin corifollitropin (Elonva) was approved for use in assisted reproduction, and welcomed by patients as the single injection allowed ovarian stimulation over 7 days without need for multiple injections. Consequently, another rFSH dosing algorithm was devised to incorporate Elonva, and these cycles were compared to standard rFSH agents, Gonal-f and Puregon. Initiated Elonva cycles (n = 165) were compared with 972 cycles initiated with standard rFSH. Elonva replaced standard rFSH dosages across the 200-400 IU range, but provided equivalent oocyte retrieval numbers and live birth outcomes. Elonva is considered risky for women whose antral follicle count is =20 follicles, and was inadvertently administered contra-protocol in 19 cycles with =20 follicles. However, while oocyte retrieval numbers were higher, raising risk for OHSS, no actual cases ensued. Taken together, this indicated that Elonva was equivalent to standard rFSH stimulation, and consequently has been added to the rFSH algorithms for medium to lower antral follicle counts and represented by green colour coding in the existing PIVET algorithmic charts.